KOMODIFIKASI DALAM PROGRAM TELEVISI INDONESIAN IDOL SEASON 10 - Tatik Inggriani, Ni Made; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
Today's mass media is not only a public space, but it can be a form of economic interest that fights in it. The development of the media industry often plays a profit strategy by comodification the form of impressions to gain a rating advantage. Television that is a mass media using public frequencies should be able to be wiser in airing a broadcast. The results of research in the Program Indonesian Idol Season 10 has been constructed in such a way as to conform to market price standards with various forms of commodification ranging from content, audiences, and labour. This research is qualitative research using the semiotic analysis of John Fiske and supported by the economy politic media theory proposed by Vincent Moscow. The overall commodification that occurs can ultimately benefit especially in the broadcast media. Keywords: Comodification, Television, Media Economy Politic, Indonesian Idol